INTEGRASI EDUKASI PEMILAHAN SAMPAH ORGANIK DAN NON-ORGANIK DENGAN PROGRAM ANAK PEDULI LINGKUNGAN DI SEKOLAH DASAR - Hafidoh; Anna Maria Oktaviani; Sakilatun Nabila (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the effectiveness of integrating organic and non-organic waste sorting education with the Children Care for the Environment program in improving elementary school students' knowledge, attitudes, and behavior towards waste management. The study used a quantitative approach with a quasi-experimental design involving 200 students in grades IV, V, and VI from five public elementary schools. The educational program was implemented for four weeks through interactive lectures, visual media, simulations, and direct practice of waste sorting. The research instruments were a Likert scale questionnaire and a behavioral observation sheet that had been tested for validity and reliability. The results showed a significant increase in student knowledge, with an average score increasing from 41.7 to 78.9 (p < 0.001). Students' attitudes towards environmental awareness also increased significantly from an average score of 2.9 to 4.2 (p < 0.001). In addition, students' waste sorting behavior experienced a significant change, indicated by an increase in the percentage of students who were able to sort waste correctly from 23% to 72%. Correlation analysis showed a significant positive relationship between students' knowledge, attitudes, and behavior. This finding indicates that integrating waste sorting education with the Children Caring for the Environment program is an effective environmental education strategy in elementary schools.